Scratch 2.0 game development hotshot : 10 engaging projects that will teach you how to build exciting games with the easy-to-use Scratch 2.0 environment /: 10 engaging projects that will teach you how to build exciting games with the easy-to-use Scratch 2.0 environment. (2014) - Pul, Sergio van; Chiang, Jessica
No abstract available